Risk of Children Violence Abuses Based on Social And Demographic Factors in The Slum Areas - Aristiana Prihartining Rahayu; Waode Hamsia (Faculty of Education Universitas Negeri Malang, 2020)
Nowadays more violent issues experienced by children in physical, verbal, emotional, and sexual abuses. Some factors identified as the sources of the violent issues including family dysfunction, economic factors, and misperceptions about the children. It is due to family economic pressures and disadvantageous social economic condition of the family or parent. The study used a qualitative approach with analytical descriptive technique in analysing the data. Results indicate that that residents especially women and children who live in the slum or densely populated area were subject to violent treatments on physical, psychological / emotional, and verbal abuses. These will lead to the constraints of education access services and school drop out to the children. In conclusion, there is a model of linkage between the risks of children abuses, social and demographic factors of the slum areas.